No house to call my home : love, family, and other transgressions - Berg, Ryan, 1974- (Nation Books, a member of the Perseus Books Group, 2015)
"Underemployed and directionless, Ryan Berg took a job in a group home for disowned and homeless LGBTQ (lesbian, gay, bisexual, transgender and questioning) teenagers. His job was to help these teens discover their self worth, get them back on their feet, earn high school degrees, and find jobs. But he had no idea how difficult it would be, and the complexities that were involved with coaxing them away from dangerous sex work and cycles of drug and alcohol abuse, and helping them heal from years of abandonment and abuse. In No House to Call My Home, Ryan Berg tells profoundly moving, intimate, and raw stories from the frontlines of LGBTQ homelessness and foster care. In the United States, 43% of homeless youth were forced out by their parents because of their sexual orientation or gender identity. Berg faced young people who have battled extreme poverty, experienced unbalanced opportunities, structural racism, and homophobia. He found himself ill-equipped to help, in part because they are working within a system that paints in broad strokes, focused on warehousing young people, rather than helping them build healthy relationships with adults that could lead to a successful life once they age out of foster care. By digging deep and asking the hard questions, and by haltingly opening himself up to his charges, Berg gained their trust. Focusing on a handful of memorable characters and their entourage, he illustrates the key issues and recurring patterns in the suffering, psychology and recovery of these neglected teens. No House to Call My Home will provoke readers into thinking in new ways about how we define privilege, identity, love and family. Because beyond the tears and abuse, the bluster and bravado, what emerges here is a love song to that irrepressible life force of youth: hope. "--